Definition and criteria for diagnosing primary dysmenorrhea: a modified Delphi procedure - Özcan, Habibe; Albana, Juliana; Yarde, Felicia; Dekker, Judith J M L; Roos, Eveline J; Goverde, Angelique J; van Dorp, Wendy; Ortiz, Mario I; Hewitt, Geri D; Simms-Cendan, Judith; Al-Jefout, Moamar; Cooper, Nina; et al. (Elsevier, 2026)
Objective: To achieve consensus on a standardized definition and diagnostic criteria of primary dysmenorrhea. Methods: A modified Delphi procedure was conducted from January to October 2024. Consensus on a question was predefined as a rate of agreement of 70% or higher. Participants were experts defined by their clinical experience in managing patients with primary dysmenorrhea, publishing on the topic, or membership in international pediatric and/or adolescent gynecology associations. Results: Twenty of 41 invited experts participated. Three rounds were required to achieve consensus, with response rates for each round of 85%, 82%, and 86%, respectively. Experts defined primary dysmenorrhea as dysmenorrhea in absence of any pelvic pathology. Primary dysmenorrhea may not start at menarche. Onset of symptoms may be before or during menstrual blood loss. The diagnosis of primary dysmenorrhea requires the absence or low clinical suspicion of the following conditions: sexually transmitted infection, pelvic inflammatory disease, congenital uterine anomaly, endometriosis, adenomyosis, and fibroids. A pelvic examination is not required for diagnosis. Consensus was reached on using ultrasound examination (transabdominal ultrasound in non-sexually active patients or transvaginal ultrasound in sexually active patients) as the preferred initial diagnostic instrument, with magnetic resonance imaging if results are inconclusive. No minimum duration of dysmenorrhea is required. Severity assessment using a verbal multidimensional scoring system (VMSS) of grade 2 or higher is part of the diagnostic criteria for primary dysmenorrhea. Systemic symptoms are not considered to be necessary for diagnosis. Conclusion: Consensus was achieved regarding the definition and diagnostic criteria for primary dysmenorrhea.
Keywords: Adolescents; Adults; Definition; Diagnostic criteria; Primary dysmenorrhea; Pediatrics, Perinatology, and Child Health; Obstetrics and Gynaecology